The Using of Implicature in Poem by William Henry Davies - Muhammad Natsir; Bahagia Saragih; Rafika Dewi Nasution; Christine Helena Natalia (Randwick International of Social Science Journal, 2021)
This paper aims to compare and analyze the five poems that written by five different poets to find the implicature in all that poems and try to find the literal meaning behind every poem that the writer took as their data. And for this research, the writer comes with the qualitative study with the descriptive method to analyze this research, where with this method the writer attempt to describe and interpret the object of the research because the data has presented descriptively. The analysis of this research has been done with read the poem thoroughly to find the implicature from the poem then describing how the types represented in each poem, and explaining the significant differences among the five poems.